PERILAKU BERALIH MEREK KONSUMEN DALAM PEMBELIAN PRODUK OTOMOTIF - Khusniyah Purwani; Basu Swastha Dharmmesta (Journal of Indonesian Economy and Business (JIEB), 2002)
This research examined of consideration set size to switch brands in automotive purchase, called Sambandam-Lord model (1995). The results showe that the replicated research model could be applied to the observed data, but not all eleven hypotheses could be supported as the researchers expected. Six of the eleven hypotheses, have been supported, while the others have not. This condition indicates that automotive brands switching behavior occurred because of the three factors mentioned in the model, i.e. (1) prior experience, (2) product knowledge, and (3) media search, and other factors. The intended factors which have not been revealed were found as a desire to have newly manufactured cars, a desire to try other brands, and boredom of the owned car, need to be considered for further research.Keywords: Brand switching, consideration set size, prior experience, product knowledge, media search, retailer search, and satisfaction.